A CRITICAL REVIEW ON DIFFERENT DASHAMOOLADI KWATH YOGA - Parmar, Neha; Singh, Suman; Patel, Bhupesh (International Journal of Ayurveda and Pharma Research, 2015)
Dashamoola is useful herbal combinationof roots of ten plants. This combination has been used in various dosage forms i.e. Taila, Ghrit, Avaleha, Kshirapaka, Arishta, Kwatha etc., but Kwatha form is extensively described and used by ancient and recent Acharyas. The aim of the study is to compile Dashamoola Kwatha formulations along with the selection and role of Prakshep dravya in different diseased conditions regarding Dashamoola and Dashamooladikwatha (Dashamoola kwatha with additional ingredients). In this review study, Dashamoola Kwatha; with Prakshep dravya and Dashamoola Kwatha with other additional Dravyas which are up to ten were selected from 32 classical texts. Total 30, 38 and 99 references were found for Dashamoola kwatha, Dashamoola kwatha with Prakshep dravya and Dashamooladikwatha respectively without repetition. Dashamoolakwatha is found most effective on Amajanya, Avruttavatajanya, Santarpanottha, Amapakwashyasamuttha vyadhis. By adding additional dravyas either Kwathya or Pakshepa to Dashamoola kwatha efficacy of the formulations and its spectrum is found to be increased.